Fetal macrosomia, polyhydramnios and cardiac anomalies may be helpful to predict poor outcome in neonate – case report of a possible fetal RASopathy with sonographic and neonatal findings and genetic evaluation - Respondek-Liberska, Maria; Węgrzynowski, Jerzy; Oszukowski, Przemysław; Gulczyńska, Ewa; Nykiel, Elżbieta; Jakubowski, Lucjusz; Grzesiak, Mariusz; Czichos, Ewa; Romanowicz, Hanna (Prenatal Cardiology, 2017)
This is a case report about very rare findings in 2nd half of pregnancy (after normal 1 trimester scan ) at 18th week of gestation fetal macrosomia was detected unrelated to maternal diabetes, and acceleration fetal growth later on with unusual cardiac abnormalities (fetal cardiomegaly, cardiomyopathy, partial abnormal venous connection ). Progressive features of congestive heart failure with polyhydramnios in a fetus with estimated 5500 g predicted a poor outcome and severe neonatal condition, which was presented and discussed with the parents to be. Casearean section was performed at 33rd weeks of gestation due to maternal dyscomfort, severe legs edema and her tachypnoe. Baby boy was delivered with birth weight of 5050g, Apgar 4 with mutiple tumors. Conservative care was introduced and neonated died on the 3rd day. Differential diagnosis was discussed with special attention to Costello syndrome however without proved by genetic make-up from neonatal blood.